Currency Matching and Carry Trade by Non-Financial Corporations - Gábor Kátay; Harasztosi Péter (Publications Office of the European Union, 2017)
The paper investigates firms' willingness to match the currency composition of their assets and liabilities and their incentives to deviate from perfect matching. Using detailed information at the loan contract level for the Hungarian non-financial corporate sector, the paper provides strong evidence to support the theory that currency matching plays a role in exporters' debt currency choices. However, natural hedging is not the primary motivation for firms to choose foreign currency: it explains less than 5 per cent of the overall new corporate foreign currency loans contracted by exporters and less than 2 per cent of the aggregate new foreign currency bank loans. Besides hedging, our results suggest that both carry trade and diversification strategies are relevant factors in firms' currency-of-denomination decisions.
Keywords: G01; G11; G32; F31; F34; 330; borrowing decisions; currency mismatch; carry trade; financial crisis